2007
DOI: 10.1016/j.molcel.2007.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin- and ATP-Independent Proteolytic Turnover of p21 by the REGγ-Proteasome Pathway

Abstract: We previously demonstrated that the proteasome activator REGgamma directs degradation of the steroid receptor coactivator SRC-3 by the 20S proteasome in an ATP- and ubiquitin-independent manner. Our efforts to identify additional endogenous direct targets of the REGgamma proteasome revealed that p21(Waf/Cip1), a central cyclin-dependent kinase inhibitor, is another endogenous target. Gain-of-function analysis, RNAi knockdown, REGgamma-deficient MEF analysis, and pulse-chase experiments substantiate that REGgam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
286
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 249 publications
(305 citation statements)
references
References 39 publications
14
286
1
4
Order By: Relevance
“…We further examined the regulation of c-Myc by REGγ using REGγ − / − (REGγ knockout) murine embryonic fibroblasts (MEFs). As expected, REGγ deficiency significantly increased the protein levels of c-Myc as well as the reported REGγ substrates p53 and p21, 10,30 but had no measurable effect on the protein levels of AKT and LSD1 (Figure 2a). This result was confirmed using an immunofluorescence staining assay (Figure 2b).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…We further examined the regulation of c-Myc by REGγ using REGγ − / − (REGγ knockout) murine embryonic fibroblasts (MEFs). As expected, REGγ deficiency significantly increased the protein levels of c-Myc as well as the reported REGγ substrates p53 and p21, 10,30 but had no measurable effect on the protein levels of AKT and LSD1 (Figure 2a). This result was confirmed using an immunofluorescence staining assay (Figure 2b).…”
Section: Resultssupporting
confidence: 76%
“…6 REGγ is emerging as an alternative pathway to target intact proteins for degradation independent of the 26S proteasome. 7,30 Thus, we examined whether REGγ has any role in c-Myc protein turnover. Our data showed that ectopic expression of REGγ resulted in a marked reduction in c-Myc protein in a dosedependent manner (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations